Pengaruh Transaksi Online (E-Commerce), Modal Usaha Dan Penggunaan Sistem Informasi Akuntansi Terhadap Pendapatan UMKM Di Kecamatan Metro Barat - Urohmah, Vivi Aulia; Zanaria, Yulita; Kurniawan, Angga (Universitas Muhammadiyah Metro, 2022)
This study aimed to examine the effect of online transactions (E-commerce), business capital, and the use of accounting information systems on UMKM income in West Metro District. The type of research used in this study was explanatory with a quantitative approach. The subjects of this research were UMKM actors in West Metro District with a total of 95 respondents. From these tests it can be concluded that: Online Transactions (E- commerce) had a positive effect on UMKM income in West Metro District, Business Capital had a positive effect on UMKM income in West Metro District, the use of Accounting Information Systems had a positive effect on UMKM income in West Metro District. For the public or the public, the results of this study were expected to increase public knowledge about the effect of Online Transactions (E-commerce), Business Capital, and the use of accounting information systems on UMKM income in West Metro District. So that the community, especially UMKM actors, can know clearly about the income of UMKM.